SWAN_ASSIST: Semi-Automated Detection of Code-Specific, Security-Relevant Methods - Piskachev, Goran; Nguyen Quang Do, Lisa; Johnson, Oshando; Bodden, Eric (2019 34th IEEE/ACM International Conference on Automated Software Engineering (ASE))

AuthCheck: Program-State Analysis for Access-Control Vulnerabilities - Piskachev, Goran; Petrasch, Tobias; Späth, Johannes; Bodden, Eric (Lecture Notes in Computer Science)

Softwareentwicklung wie am Fliessband - Koch, Thorsten; Meyer, Matthias; Fazal-Baqaie, Masud; Runschke, Hubert (Software Engineering 2020 (SE 2020))

Coaching on the Job bei Unternehmen des Maschinen- und Anlagenbaus - Wissenslücken schließen zur Weiterpflege modernisierter IT-Anwendungen - Fazal-Baqaie, Masud; Strüwer, Jan-Niclas; Schmelter, David; Dziwok, Stefan (Projektmanagement und Vorgehensmodelle 2019 (PVM 2019))

Designing and Integrating IEC 62443 Compliant Threat Analysis - Fockel, Markus; Merschjohann, Sven; Fazal-Baqaie, Masud; Förder, Torsten; Hausmann, Stefan; Waldeck, Boris (European System, Software & Service Process Improvement & Innovation Conference (EuroSPI 2019))

Codebase-adaptive detection of security-relevant methods - Piskachev, Goran; Do, Lisa Nguyen Quang; Bodden, Eric (Proceedings of the 28th ACM SIGSOFT International Symposium on Software Testing and Analysis)

Was fehlt (bisher) um Apps sicher zu entwickeln? - Prozesse, Werkzeuge und Schulungen für sichere Apps by Design - Altemeier, Katharina; Becker, Matthias; Dziwok, Stefan; Koch, Thorsten; Merschjohann, Sven (Projektmanagement und Vorgehensmodelle 2019 (PVM 2019))

Safety Requirements Engineering for Early SIL Tailoring - Fockel, Markus
Der hohe Grad an Innovation in mechatronischen Systemen führt zu sogenannten Cyber-Physical Systems (CPS). Diese haben eine komplexe Funktionalität und Kommunikation. Wie sicherheitskritisch solche Systeme sind, wird durch sogenannte Sicherheits-Integritätslevel (SIL) kategorisiert, die durch Normen wie der ISO 26262 definiert werden. Ein bestimmter SIL beschreibt nicht nur die Höhe des Gefährdungsrisikos, sondern diktiert auch den erforderlichen Grad an Sorgfalt bei der Entwicklung des Systems. Ein hoher SIL erfordert die Anwendung von Safety-Maßnahmen mit einem hohen Sorgfaltsgrad in allen Phasen der Entwicklung und impliziert daher einen hohen Safety-Aufwand. SIL-Tailoring ist ein Mittel um den Safety-Aufwand zu reduzieren, indem man Subsystemen geringere SILs zuordnet, falls sie von kritischeren Subsystemen getrennt sind oder redundante Safety-Anforderungen erfüllen. Um den nötigen Safety-Aufwand zu planen, sollten Möglichkeiten für SIL-Tailoring so früh wie möglich identifiziert werden - d.h. bereits in der Anforderungsanalyse. Durch die Komplexität von CPS, ist es schwierig valide SIL-Tailorings zu finden. Die Validität von SIL-Tailorings muss durch Analyse von Fehlerpropagierungspfaden geprüft und durch Argumente im Safety Case begründet werden. Der Beitrag dieser Dissertation ist ein systematischer, tool-unterstützter SIL-Tailoring-Prozess, der im Safety Requirements Engineering angewendet wird. Der Prozess nutzt eine modell-basierte, formale Anforderungsspezifikation und stellt einen Katalog von Anforderungsmustern bereit. Basierend auf diesen Anforderungen werden Fehlerpropagierungsmodelle generiert und Subsystemen automatisch SILs zugeordnet. Das minimiert den Sicherheitsanalyseaufwand. Aus den generierten Ergebnissen wird automatisch ein Safety Case mit Argumenten für die SIL-Tailoring-Validität abgeleitet.

Threat Analysis in Practice - Systematically Deriving Security Requirements - Fockel, Markus; Merschjohann, Sven; Fazal-Baqaie, Masud (19th International Conference on Product-Focused Software Process Improvement (PROFES 2018))
With the growing number of incidents, the topic security gains more and more attention across all domains. Organizations realize their lack of state-of-the-art security practices, however, they struggle to improve their software lifecycle in terms of security. In this talk, we introduce the concept of security by design that implements security practices within the whole software lifecycle. Based on our practical experience from industry projects in the regulated industrial automation and unregulated classical IT domain, we explain how to perform a threat analysis and how to integrate it into the software lifecycle.

Model-Driven STEP Application Protocol Extensions Combined with Feature Modeling Considering Geometrical Information - Koch, Thorsten; Holtmann, Jörg; Lindemann, Timo (Revised Selected Papers of the 5th International Conference on Model-Driven Engineering and Software Development)
Original equipment manufacturers (OEMs) build mechatronic, variant-rich systems using components from several suppliers in industry sectors like automation. The OEMs have to integrate the different components to the overall system based on a virtual layout. For this purpose, the suppliers provide geometrical information via the standardized exchange format STEP. Beyond the geometrical information, the OEMs need additional logical and technical information for the integration task as well as the variant handling. For that reason, STEP provides an extension mechanism for extending and tailoring STEP to project-specific needs. However, extending STEP requires extending several capabilities of all involved tools, which prevents the project-specific utilization of the STEP extensions mechanism. In order to cope with this problem, we presented in previous work a model-driven approach enabling the flexible specification of STEP extensions and particularly the automatic derivation of the required capability extensions for two involved tools. Nevertheless, the OEMs still need to apply several engineering tools from different domains to consider logical as well as geometrical constraints between product variants. In this paper, we hence combine our previous approach with extended feature models that consider conventional logical and particularly geometrical information, thereby enabling a holistic product line engineering for mechatronic systems. By means of an automation production system example, we illustrate how OEMs can orchestrate their overall supply and development processes through the combination of both approaches.